An overview of allergy and sinusitis - Nicholus Magongwa; Natalie Schellack (South African Family Practice)
Allergic diseases affect many people across the globe. They are considered to significantly disturb the quality of life of the people who are affected, creating personal and economic predicaments. Some of the most commonly diagnosed allergic diseases include atopic dermatitis, rhinitis, allergic conjunctivitis and sinusitis. Some conditions, such as eosinophilic esophagitis, are on the rise and are being diagnosed across all continents except for Africa. The use of antihistamines has been the mainstay of therapy for most allergic conditions, except for other conditions that require corticosteroids, or in severe allergic conditions such as anaphylaxis where antihistamines are ineffective as main therapy. It is important to consider first versus second-generation options when treating allergic diseases, also bearing in mind the duration of therapy and any comorbid conditions that a patient might have. This article provides an overview of these conditions and their current management options.